Synthetic fuels production by graphite-assisted electrolysis - Fernandes, Vitor (2019)
ABSTRACT: Hydrogen produced by water electrolysis is considered as the best energy carrier to adjust the balance between the generation of power source by renewable primary energy and energy demand for end-use. Further advantages are foreseen with the use of carbon-assisted electrolysis. This is due to the electrochemical participation of carbon in the reaction, the electrolysis process would potentially require about 1/3 the electrical energy with the balance of 2/3 coming from the chemical energy of carbon in comparison with conventional water electrolysis where all the energy input is electric. Carbon is oxidized to CO2 on the anode and hydrogen is produced at the cathode. Generally, carbon sources for anodic reaction are graphite, activated carbon and coal. In this work, low temperature electrochemical gasification of graphite in alkaline and acid solutions was explored, taking into account experimental conditions where the faradaic overall current has a significant contribution from carbon oxidation reactions. Results indicate adequate molar gases fraction for the production of syngas and the production of small chain hydrocarbons, obtained at laboratory prototype level.